Assessing Progress in Urban Climate Adaptation: A Review of Indicators for Heat‐ and Water‐Sensitive Urban Development - Nisha Patel; Britta Jänicke; René Burghardt; Stenka Vulova; Florian Otto (Climate Resilience and Sustainability)
ABSTRACT An increasing number of cities in Germany and Europe are formulating adaptation strategies to address the consequences of climate change. Nevertheless, quantifying whether these strategies contribute to alterations in urban infrastructure and promote climate‐sensitive urban development is challenging. This article aims to explore possible urban climate adaptation indicators (UCAIs) from literature suitable for assessing the implementation of heat‐ and water‐sensitive urban development measures in local municipalities, with a focus on Germany. In addition to a literature review, workshops and discussions with experts from Germany complemented and deepened the indicator selection process. As a result, we identified 27 indicators, which were grouped into 5 key areas: (1) surface and urban overheating indicators; (2) building type and structure indicators; (3) green infrastructure indicators; (4) soil‐sealing indicators; and (5) water‐sensitive urban development indicators. Only a few manage to map several adaptation measures, avoiding conflicts with other urban planning objectives, can be derived for cities at the national level and show promise for capturing small‐scale adaptation measures in the city. We concluded that, in particular, the green infrastructure and soil‐sealing indicators, such as green cover, access to greenery and green supply have a high potential to meet heat‐ and water‐sensitive urban development goals, while avoiding conflicts of objectives and trade‐offs. Overall, this review underscores the necessity for additional research and testing to formulate practical and effective indicators for capturing heat‐ and water‐sensitive aspects of urban development.